The Divine Idea of the Self and Contemporary Culture - Jacob Phillips (Religions)
Taking as its point of departure Pope Benedict XVI’s comment that ‘[e]ach of us is the result of a thought of God’, this article explores how the divine idea of the self bears promise for enabling a Catholic theological response to certain features of contemporary Western culture. This cultural setting is discussed first, using the interpretations of Philip Rieff and Carl R. Trueman, and their conceptualities of ‘psychological man’ and ‘expressive individualism’. The dominant contemporary view of human identity thus presented is markedly individualistic, being focused on an inward sense of self. The dominant approach to human meaning is similarly individualistic, being the satisfaction or expression of that sense of self. While both Rieff and Trueman point to a widespread loss of religious faith as pivotally important to for the emergence of these cultural paradigms, they mostly leave aside questions regarding the truth claims of specific religions in responding to them. Secondly, the scholastic doctrine of the divine ideas is discussed, with a view to presenting an alternative approach to human identity and meaning based on the contention that each human person ‘is the result of a thought of God’. Thirdly, the article concludes by drawing out the notions of identity and meaning implied by this doctrine, along with its inextricable relation to a specifically Catholic understanding of God. This understanding includes within it a distinct approach to human sociality in Christ, which answers directly to the individualism of contemporary culture, as outlined by Rieff and Trueman.